AUDIO COMPRESSION USING WAVELET TRANSFORM - Swapnil T. Dumbre; Sheetal S. Gundal (International Journal of Innovations in Engineering Research and Technology, 2021)
Audio Compression is one of the basic technologies of the modern telecommunication age. Compression is the technique to convert high input data stream into smaller size. Audio coding gives us the digital form of audio with as few bits as possible and also maintains the quality. the reduction in bit rates conserve bandwidth .Audio coding is used in various applications such as digital broadcasting ,high quality audio for satellite transmission , internet audio or music database where the high quality audio signals bit rate is reduced without compromising the quality of the signal. The technology proposed to achieve the design and implementation of audio compression using discrete wavelet transform technique. The efficiency performance of the audio encoding methods has been measured using compression ratio as well as peak signal to noise (PSNR) ratio, SNR.